Investigating the characteristics of a digitally agile organizational structure for construction companies - Nasiri, Aran. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
As the architecture, engineering, and construction (AEC) industry embraces digital transformation, the need for digitally agile construction organizations (DACOs) becomes more tangible. According to the literature, the structure of a company’s organization may have an impact on its digital agility. However, no studies have been conducted to investigate the relationship between construction firms’ organizational structures and their business models’ digital agility. This study seeks to fill this gap by conducting exploratory sequential mixed-method research, beginning with the collection of qualitative data from the literature and continuing with in-depth semi-structured interviews with experts. Following that, directed content analysis is conducted on the qualitative data to identify recurring themes in the context of construction companies’ digital transformation, provide a hypothetical definition for digitally agile organizational structure, create a hypothetical model based on defined latent variables, and define measurement factors. Then, a questionnaire is created to put the hypotheses to the test. Partial least squares structural equation modeling (PLS-SEM) is used for this test. According to the findings, a digitally agile organizational structure is less formalized, complex, and highly integrated, and it fosters the digital agility of a construction company’s business model while also providing a fertile environment for agile leadership. Furthermore, construction companies must develop a digital organizational culture through educational programs in order to reduce employee resistance to digital transformation and communicate the change to them. This study adds to the body of knowledge in the field of organizational studies in the contexts of construction management and digital transformation by providing insights into DACOs and paving the way for future research on the subject.
Keywords: Architecture.; Engineering.; Construction.; Information technology.